Efficacy of probiotics in outcome of acute watery diarrhea in children aged 06 months to 12 years admitted to the pediatrics department of Bacha Khan Medical Complex, Swabi - Ullah, Muhammad Zabih; Gul, Haji; Asma, Bibi; Inayatullah; Rizwan, Muhammad; Rehman, Sijad Ur (International Journal of Pathology, 2025)
Background: Acute watery diarrhea (AWD) affecting children contribute to high rates of morbidity and mortality in both developed and developing nations. Use of probiotics, especially Lactobacillus acidophilus, has been suggested as an additional therapeutic option in the management of childhood diarrhea. This study aimed to evaluate the effectiveness of probiotics in treating diarrhea in children aged 06 months to 2 years. Methods: A total of 552 children, aged between 6 months and 12 years, who were diagnosed with severe watery diarrhea, participated in this study. Out of these, 300 children took daily doses of L. acidophilus for five consecutive days, while the remaining 252 children were given a placebo. Initial stool specimens were obtained from all participants to detect the presence of Giardia lamblia, Entamoeba histolytica, and Ascaris lumbricoides. The primary outcomes assessed included the duration of diarrhea, hospital stay length, stool consistency, frequency of bowel movements, electrolyte imbalances, and the time taken for symptom resolution. Statistical analysis was performed using t-tests for continuous variables, chi-square tests for categorical variables, and regression models to examine factors contributing to positive clinical outcomes. Results: Children who received probiotics showed a marked improvement in duration of diarrhea (42.50 ± 11.80 hours vs. 58.40 ± 27.50 hours) and reduced hospital stay (66.10 ± 9.80 hours vs. 81.50 ± 27.00 hours), with p-values of < 0.001 and 0.008, respectively. They also showed quicker improvements in bowel movement frequency and stool consistency, along with fewer electrolyte disturbances (p < 0.001). The clinical efficacy of the probiotic was 91.0%, significantly higher than the control group’s 79.9% (p = 0.021). Conclusion: Our findings strongly advocate for the effectiveness of probiotics in treating diarrhea in children.